Kontribusi Istri Nelayan Dalam Meningkatkan Pendapatan Keluarga di Desa Sebuntal Kecamatan Marangkayu Kabupaten Kutai Kartanegara - Irfan Taufiq; Fitriyana; Gusti Haqiqiansyah (Jurnal Multidisiplin Madani, 2022)
This study aims to determine the household income of fishermen's wives in increasing family income. The research method  used is purposive sampling with quantitative descriptive data analysis techniques.  The results showed that the total average income in households using bubu fishing gear was Rp. 4,570,000 / month and rawai fishing gear was Rp. 5,870,000 / month. Meanwhile, there were no contributions from other family members The contribution of fishermen's wives who worked as salted fish processors was different. Where the highest contribution of wives is the fisherman's wife who usesn bubu fishing gear by 55%.  The value is in the interval of 50.01% - 100% which means that the contribution of fishermen's wives who use bubu fishing gear is very influential and important inhelping to increase the income of fishermen's families with bubu fishing gear.